Jesus and the forgiveness of sins an aspect of his prophetic mission - Hagerland, Tobias, 1975- (Monograph series (Society for New Testament Studies) ;, 2011)
"The Gospels record that Jesus purported to forgive sins. What significance would such a claim have had for his contemporaries and what would the implications have been for his identity as a first-century popular prophet? Tobias Ha;gerland answers these questions and more as he investigates the forgiveness of sins in the mission of the historical Jesus. The Gospels are interpreted within the context of first-century Judaism as part of a broader reconstruction of Jesus' career as a healer and prophet, and rhetorical criticism is introduced as a tool for explaining how the gospel tradition about Jesus and forgiveness developed. Ha;gerland combines detailed exegesis and rigorous methodology with a holistic view of the historical Jesus, evaluating recent scholarship about first-century Jewish prophets and utilizing previously neglected textual evidence to present a thorough investigation of the theology of forgiveness in early Judaism and primitive Christianity"--